ANALISIS PERMASALAHAN GURU BIMBINGAN DAN KONSELING DALAM PELAKSANAAN KUNJUNGAN RUMAH - Monica Arlita; Lusia Januarti; Nadila Farahita; Ifnaldi; Edi Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Home visits are one of the supporting services in guidance and counseling aimed at obtaining direct information regarding students’ family and environmental conditions as a basis for understanding and addressing the problems they experience. The implementation of home visits plays an important role in establishing collaboration between schools and families to support students' optimal development. However, in practice, guidance and counseling teachers often encounter various obstacles that hinder the effective implementation of this service. This study aims to analyze the problems faced by guidance and counseling teachers in conducting home visits. The study employed a qualitative approach with a descriptive method. The research participants consisted of guidance and counseling teachers as the main informants, while school principals, homeroom teachers, and parents served as supporting informants selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that guidance and counseling teachers faced several challenges in implementing home visits, including limited time due to heavy workloads and counseling responsibilities, excessive work demands, low levels of parental understanding and participation in guidance and counseling services, limited operational funding and supporting facilities, geographical barriers that complicated access to students’ residences, and insufficient institutional support from schools. The study also found that these challenges were influenced not only by individual factors related to the counselors but also by family, school, and broader social environmental factors that interact with one another. Therefore, strengthening school policies, enhancing the professional competencies of guidance and counseling teachers, providing adequate operational support, and improving collaboration between schools and families are essential to optimize the implementation of home visit services and support students’ overall development.